Studi tentang Keputusan Pembelian Sepeda Motor Merek Honda di Semarang - Frendy Prasetya; Sri Rahayu Tri Astuti (Conference In Business, Accounting, And Management (CBAM), 2012)
Increasingly intense competition among companies in the industrial motor manufacturer of motorcycles in Indonesia has caused the decline in the level of customer and product purchases, and the profitability of most companies motorcycle manufacturer in Indonesia. It is also experienced by PT Astra Honda Motor in its motorcycle product as a market leader in the motorcycle industry. To re-gain more new customers while maintaining old customers, and obtain the level of purchases of Honda motorcycles and high profitability in the company, the need for efforts to improve the customer buying decision, because the purchase decision is a major factor in increasing sales and profitability. In this study, we use differentiation, promotion, and positioning as an independent variable to be studied how they affect purchasing decisions. The results showed that the coefficient of determination shown in the Adjusted R Square of 0.704, which means that its influence purchasing decisions can be explained by the three independent variables in this research that differentiation, promotion, and positioning of 70.4%, and the remaining 29.6% canbe explained by other variables outside the model of this research. Partially based on the results of t test variables in this study has positive and significant in which promotion has the biggest influence on purchase decisions , while positioning has the smallest influence on purchase decisions.Keywords: Differentiation, Promotion, Positioning, Purchase Decision